From risk to resilience: A user-centered water monitoring and early warning system - Alemayehu, Sintayehu; Tegegne, Getachew; Dejene, Sintayehu Workeneh (2025)
The lowland regions of Ethiopia are facing persistent drought and various climate challenges, which threaten the livelihoods of communities that rely on livestock. To help these communities adapt, there’s a pressing need for a new approach to water monitoring. The Alliance of Bioversity International and CIAT have developed and implemented a user-centered livestock water monitoring and early warning system designed to build climate resilience in Ethiopia’s drylands. Calibration and validation of the water balance model showed that it effectively replicated observed water depths at various gauging waterpoints. Ungauged waterpoints were modeled using a hybrid of spatial proximity and physical similarity methods. By integrating seasonal and sub-seasonal climate forecasts with the calibrated and regionalized water balance model, the statuses of waterpoints (Good, Watch, Alert, Near-dry, and Seasonally Dry) and pastoral advisory services were effectively communicated to the local community through SMS, Community Information Centers, and media programs. One of the standout features of this initiative is its focus on inclusivity and human-centered design, which ensures it meets the specific needs of the community. By utilizing satellite data and citizen science, alongside advanced forecasting techniques, the system delivers practical insights into water resources. Feedback from field surveys indicates that the digital water monitoring system has been well received and is making a positive impact on climate resilience in the region. It fosters sustainability by encouraging collaboration between government bodies and local stakeholders. The study highlights that sharing real-time water information and advisory services can significantly improve water management and reduce conflicts over resources.